Antidiarrheal Effect of DLBS1Y62, a Bioactive Fraction of Uncaria gambir Roxb. Dried Sap Extract, in Wistar Rats - Wibowo DA; Nailufar F; Tjandrawinata RR (Dove Medical Press, 2021)
Dicky A Wibowo,1 Florensia Nailufar,1 Raymond R Tjandrawinata2 1Animal Pharmacology Section, Dexa Laboratories of Biomolecular Sciences (DLBS), PT Dexa Medica, Cikarang, 17550, Indonesia; 2Dexa Laboratories of Biomolecular Sciences (DLBS), PT Dexa Medica, Cikarang, 17550, IndonesiaCorrespondence: Raymond R TjandrawinataDexa Laboratories of Biomolecular Sciences (DLBS), PT Dexa Medica, Industrial Estate Jababeka II, Industri Selatan V Block PP No. 7, Cikarang, 17550, IndonesiaTel +62-21-89841901Fax +62-21-89841905Email raymond@dexa-medica.comBackground: Diarrhea is a common health problem worldwide, especially in developing countries. It is the second leading cause of mortality for children. Uncaria gambir Roxb. extract has been used to treat diarrhea and dysentery, and as an astringent medicine, in Asian countries. Here, we investigated the antidiarrheal effect of DLBS1Y62, which is the bioactive fraction of dried sap extract from U. gambir, using castor oil-induced diarrhea and castor oil-induced enteropooling in rats.Methods: DLBS1Y62 was obtained by crushing and milling the dried sap extract of U. gambir leaves. Male Wistar rats, 2- 3 months old, weighing 200- 250 g (n=30), were used for this study. Negative controls received 0.05 mL purified water. Positive controls were treated with 2 mg/kg BW loperamide orally as a suspension. Groups I, II, and III received 6.25, 12.5, and 25 mg/kg BW DLBS1Y62, respectively. Group IV received a combination of 6.25 mg/kg BW DLBS1Y62 and 20 mg/kg BW attapulgite. Diarrheal onset and frequency were observed; then, the weight and volume of intestinal contents were measured.Results: DLBS1Y62 at all dose levels and in combination with attapulgite could inhibit the formation of further fecal forms of diarrhea, without delaying the onset of diarrhea. The rats that received DLBS1Y62 25 mg/kg BW had the lowest frequency of diarrhea and average intestinal contents compared with the treatment and negative control groups. DLBS1Y62 at a dose of 25 mg/kg BW also gave similar results to 2 mg/kg BW loperamide as a positive control in reducing diarrheal frequency and intestinal content.Conclusion: The results of this study suggest that DLBS1Y62, particularly at a dose of 25 mg/kg BW, containing tannin as a compound, may become an alternative treatment for diarrhea.Keywords: Uncaria gambir Roxb., DLBS1Y62, diarrhea, rats